Comparing Matthew and Luke in the Light of Second Temple Jewish Literature - Brooke, George J. (Journal for the study of the New Testament, 2018)
This article argues that Luke provides a framework for his gospel narrative about Jesus that is based on the institution of the Temple but that the narrative as a whole is filled with instability marked by features of inclusiveness, whereas Matthew provides a framework of hope in the fulfilment of prophetic texts but that the central gospel narrative as a whole is marked by a restricted and restricting structure based on the Torah. As such the two gospels variously play with features of Jewish societal self-understanding that are also, at least partially, represented in 1 and 2 Maccabees, or in the sectarian scrolls found in the Qumran caves. The insights of C. Lévi-Strauss, as recently adapted for reading narratives by J.W. Rogerson, are used as the basis of a reading strategy.